(untitled) (Revista Española de Fisiología, 1993)
Growth factors (EGF and IGF-I) have different actions on mammalian cells such as proliferation and differentiation. The effect of EGF and IGF-I was examined on in vitro matured bovine oocytes. Immature oocytes were obtained by follicular aspiration from slaughtered heifer ovaries and classified in two groups, with or without cumulus cells. Oocytes (n = 1,037) were cultured in a serum-free media (TCM-199) for 24 hours at 39 degrees C in absence of hormones and were divided in 5 treatments: control, EGF (20 ng/ml and 50 ng/ml), IGF-I (100 ng/ml) and EGF + IGF-I (50 ng/ml + 100 ng/ml). Results suggest that the EGF + IGF-I treatment increases significantly (p < 0.01) the maturation rate (60.3%) as compared to control medium (36.5%) in cumulus cell-enclosed oocytes. No significant differences were observed between the treatments in the denuded oocytes. The effect of EGF + IGF-I added to the maturation media seems to be mediated by the surrounding cumulus cells and enhanced the in vitro maturation rate on cumulus cell-enclosed bovine oocytes.